Metode, Pendekatan Ilmiah, Model Pemikiran Dan Teori Revolusi Paradigma Thomas Samuel Kuhn - Shelly Alvareza Zazkia (Scidac Plus, 2021)
Thomas S. Khun made a big contribution to the history of the philosophy of science, namely the broad realization of the theories he initiated in the social sciences. In social sciences such as education or politics in terms of figure of speech or parallelism, Kuhn's theory has been added. Kuhn considers history as the main lens in an effort to study fundamentals via epistemology. The purpose of this research is to find out the biography of Thomas S Kuhn, to explore the philosophical basis of Thomas S Kuhn's thinking, to find out the type of Thomas S Kuhn's paradigm and to find out the contribution of Thomas S Kuhn's Paradigm . This article was compiled using the library research method or literature study. The results of the study show that the scientific dynamics of education is able to contextualize Thomas S. Kuhn's thoughts about the process of the birth of science to be able to reach and gain knowledge and knowledge through a combination of problem solving activities of an educator which has a major influence in helping students achieve their expectations.